Transformasi Digital Manajemen Talenta ASN: Penguatan Sistem Merit Kementerian Kelautan dan Perikanan - Raden Andaru Rahadi Basuki; Asropi (Cantaka: Jurnal Ilmu Ekonomi dan Manajemen, 2026)
The merit system assessment of the Ministry of Marine Affairs and Fisheries (KKP), categorized as Very Good, does not yet fully reflect the readiness of digital transformation in civil servant talent management. This study analyzes the gap between civil servant talent management policy design and digital transformation practices supporting the merit system at KKP. The study applies a descriptive qualitative approach using systematic literature review (SLR) and policy document analysis. The data consist of secondary sources, including regulations, policy documents, institutional reports, KKP Human Capital Management policy materials, technical guidance on government talent management, and scholarly literature on e-HRM, talent analytics, civil servant talent management, and public sector digital transformation. The findings show that the main obstacles do not lie in the absence of regulation, but in fragmented talent data that creates silos across personnel platforms, weak system interoperability, limited use of competency and performance data in succession decisions, and insufficient analytical capacity within the HR function. This fragmentation prevents employee, performance, assessment, competency development, certification, position history, and target-position data from forming an integrated talent profile. This study contributes a framework for strengthening merit-based and data-governed talent management that positions digitalization as a strategic mechanism for civil servant career decision-making, not merely personnel administration modernization.